1994
DOI: 10.1007/bf00313602
|View full text |Cite
|
Sign up to set email alerts
|

Loss of insulin receptor immunoreactivity from the substantia nigra pars compacta neurons in Parkinson's disease

Abstract: Immunohistochemistry using both a newly developed polyclonal, and a commercially available monoclonal, anti-insulin receptor antibody was done on the midbrain from cases of idiopathic Parkinson's disease (PD), Alzheimer's disease, amyotrophic lateral sclerosis, vascular parkinsonism and non-neurological controls. Both antibodies gave identical patterns of neuronal staining. The neurons of the oculomotor nucleus were immunopositive in all the brains. However, the neurons in the pars compacta of the substantia n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(57 citation statements)
references
References 27 publications
0
57
0
Order By: Relevance
“…Also, evidence has accumulated that brain IR promote spermatogenesis and ovarian follicle maturation via pituitary luteinizing hormone (Brü ning et al, 2000), while increasing efficiency of synaptic transmission, learning, and memory (Zhao et al, 1999;Gispen and Biessels, 2000;Zhao and Alkon, 2001). IR and IR mRNA levels were significantly lower in substantia nigra of Parkinson's disease brain compared with normal and other neurodegenerative disease brains (Moroo et al, 1994;Takahashi et al, 1996). In Alzheimer's disease brain, insulin concentration was lower, and IR signaling was impaired compared with age-matched healthy humans (Zhao and Alkon, 2001;Hoyer, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…Also, evidence has accumulated that brain IR promote spermatogenesis and ovarian follicle maturation via pituitary luteinizing hormone (Brü ning et al, 2000), while increasing efficiency of synaptic transmission, learning, and memory (Zhao et al, 1999;Gispen and Biessels, 2000;Zhao and Alkon, 2001). IR and IR mRNA levels were significantly lower in substantia nigra of Parkinson's disease brain compared with normal and other neurodegenerative disease brains (Moroo et al, 1994;Takahashi et al, 1996). In Alzheimer's disease brain, insulin concentration was lower, and IR signaling was impaired compared with age-matched healthy humans (Zhao and Alkon, 2001;Hoyer, 2002).…”
Section: Discussionmentioning
confidence: 90%
“…Dopaminergic neurons help motivate feeding behavior when glucose levels are low. This feedback loop is mediated by insulin receptors in the substantia nigra, and postmortem studies of Parkinson's disease show a loss of these receptors (11). Drugs that modulate central dopamine, such as bromocriptine, are known to affect peripheral glucose control.…”
Section: Resultsmentioning
confidence: 99%
“…In primary fetal brain cell cultures, insulin plays a role in the control of metabolism and growth (8), and clinically it has been demonstrated that patients suffering from Alzheimer's and Parkinson's diseases exhibit reduced expression of IR in the brain (9). It also has been shown that learning acutely regulates expression and tyrosine phosphorylation of the IR in the hippocampus of rats (10).…”
mentioning
confidence: 99%